Magnetic nanofibers based bandage for skin cancer treatment: a non‐invasive hyperthermia therapy - Suneet, Kaushik (Cancer Rep (Hoboken), 2020)
BACKGROUND: The treatment of non‐melanoma skin cancer and deadliest malignant melanoma skin cancer are the fifth and ninth most expensive treatments in Medicare, respectively. Moreover, the recurrence of cancer after currently available therapies, that is, surgery or radiotherapy, reduces the patient's life expectancy. AIMS: In view of this, we fabricated magnetic nanofibrous mat‐based bandage to treat skin cancer non‐invasively using an external alternating current (AC) magnetic field induced hyperthermia. METHODS: The Fe(3)O(4) nanoparticles incorporated polycaprolactone (PCL) fibers based bandages were fabricated using the electrospinning technique. The efficacy of the bandage was investigated in vitro using parental/doxorubicin hydrochloride (Dox)‐resistant HeLa cells and in vivo using BALB/c mouse model in the presence of an external AC magnetic field (AMF). RESULTS: The PCL‐Fe(3)O(4) fibrous mat‐based bandages dissipate heat energy locally on the application of an external AMF and increase the surrounding temperature in a controlled way up to 45°C in a few mins. The in vitro study confirms the elevated temperature could kill parental and Dox‐resistant HeLa cells significantly. As the activity of Dox enhanced at a higher temperatures, more than 85% of parental HeLa cells were dead when cells incubated with Dox contained fibrous mat in the presence of AMF for 10 minutes. Further, we confirm the full recovery of chemically induced skin tumors on BALB/c mice within a month after five hyperthermic doses for 15 minutes. Also, there was no sign of inflammation and recurrence of cancer post‐therapy. CONCLUSION: The present study confirms the PCL‐Fe(3)O(4) nanofibrous based bandages are unique and compelling to treat skin cancer.